The Adhesion of Modified Epoxides to Fibers. - Yulia Arkadievna, Gorbatkina (Cambridge Scholars Publishing, 2022)
This book focuses on the control interfacial strength, which is one of the most substantial problems of the science of adhesion. In particular, it discusses interfacial strength in adhesive joints in which the substrates are various fibers and the adhesives are epoxy resins modified with active diluents, rigid-chain thermoplastics, or fine fillers, and studies the change in adhesive strength during the formation of joints (during curing) and under various operating conditions. The text also analyzes the dependence of adhesive strength on modifier concentration and the existence of the synergism.